Financial Development and Income Inequality in Indonesia: A Sub-national Level Analysis - Harry Aginta; Debby Soraya; Wahyu Santoso (Economics and Finance in Indonesia, 2018)
This study constructs financial inclusion indicator and analyzes the link of financial inclusion and income inequality for 33 provinces in Indonesia. By using Fixed Effect Panel Model, we find financial inclusion appears to have insignificant effect to on inequality at national level. While at sub-national level, adding other variables such as GRDP, years of schooling, and trade openness, we find financial inclusion appears to have negative and significant impact on income inequality in manufacture and mining-based provinces, not in agriculture-based. The results suggest that financial inclusion helps to lower income inequality when economic condition encourage people to utilize financial access for productive purposes.